Perancangan Untuk Produk Origin - Indonesian Heritage Apparel - Stephanie Wijaya; Marina Wardaya (Universitas Ciputra Surabaya, 2017)
This research was done to know what people think about ORIGIN – Indonesian Heritage Apparel business idea and to research why people began to be abandoned and forgotten because it is regarded as second-class outfit, especially among young people, this thing happened because the design it self seem tradisional. Besides, the author want to change the design concept to be more modern. The research was conducted using quantitative and qualitative methods. The quantitative method using online quistionnaire which is distributed to woman aged 22-35 years who lived in Surabaya. While the qualitative method by interview to the expert usher and literature study. The result of the research shows that most of the correspondents like to buy top and dress instead of skirt and outer. Furthermore, the identity and design should represent exclusive and trusted. Media marketing is done by using bazaar and through social media.